Unwinding new therapeutic opportunities in rhabdomyosarcoma: the role of RNA helicase DDX5 - Bianconi, Valeria; Mozzetta, Chiara (Frontiers in Cell and Developmental Biology, 2025)
Rhabdomyosarcoma (RMS) is one of the most common soft tissue tumors in children and is primarily classified into two subtypes: alveolar (ARMS) and embryonal (ERMS). Among these, ARMS is the more aggressive form, often driven by chromosomal translocations that give rise to PAX3/7-FOXO1 fusion proteins, which act as oncogenic transcription factors. Despite advancements in treatment and improved survival rates over recent years, effective and targeted therapies for RMS remain a significant clinical challenge. A family of proteins known as the DEAD-box RNA helicases plays a critical role in RNA metabolism as well as in a variety of cellular processes beyond RNA regulation. Among them, DDX5 has emerged as a protein of particular interest. Aberrant expression and functional alterations of DDX5 have been reported in multiple cancers, including RMS, where its overexpression is associated with enhanced tumor growth and cancer cell proliferation. In this review, we highlight recent discoveries that position DDX5 as a promising therapeutic target in RMS, focusing on its oncogenic functions and its contribution to tumorigenesis and cancer progression.